PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA KEMAMPUAN INKUIRI PESERTA DIDIK PADA MATA PELAJARAN FISIKA SMA - Supahar, Supahar; Prasetyo, Zuhdan Kun (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2015)
Penelitian ini bertujuan mengembangkan instrumen penilaian kinerja kemampuan inkuiri mata pelajaran fisika peserta didik SMA. Instrumen terdiri atas empat paket perangkat tes yang masing-masing terdiri atas 30 butir tes termasuk 9 butir bersama yang telah divalidasi oleh ahli pendidikan fisika, ahli fisika, ahli pengukuran, dan praktisi. Instrumen diujicobakan pada 2015 peserta didik. Model respon butir politomus empat kategori digunakan untuk menganalisis data hasil uji coba menurut Partial Credit Model (PCM). Hasil penelitian menunjukkan bahwa, berdasarkan kriteria batas terendah dan tertinggi mean INFIT MNSQ, yaitu 0,77 dan 1,30 butir tes semuanya fit dengan model PCM. Tingkat kesulitan butir-butir tes berada pada rentang antara -0,83 sampai +0,84 yang berarti butir-butir tes dalam kategori baik karena nilainya di antara -2,0 dan +2,0. Fungsi informasi total tes relatif tinggi untuk kemampuan antara -2,5 sampai +2,5. Dengan demikian, instrumen yang dikembangkan dapat digunakan untuk meng-ukur kemampuan inkuiri mata pelajaran fisika siswa SMA. Hasil pengukuran menunjukkan bahwa kemampuan inkuiri peserta didik pada mata pelajaran fisika SMA di DIY berada di atas kemampuan rata-rata.Kata kunci: kemampuan inkuiri, mata pelajaran fisika SMA, Penilaian kinerja.______________________________________________________________DEVELOPING ASSESSMENT INSTRUMENT OF THE PERFORMANCE OF THE INQUIRY ABILITIES IN PHYSICS SUBJECT OF HIGH SCHOOL STUDENTSAbstract The research was to develop an assessment instrument of performance for the inquiry ability of physic subject of senior high school students. The instrument consisted of four package sets of test and each of the sets consisted of 30 test items, including 9 items that had been validated by the expert of physic education, the expert of physic, the expert of measurement and the practitioner. The instrument was tested to 2,015 learning participants. The four-category politomous item response model was implemented for the data analysis of the experiment results according to the Partial Credit Model (PCM). The results of the research showed that based on the criteria of the lowest benchmark and the highest benchmark of mean INFIT MNSQ, was 0.77 and 1.30, all of the test items had been fit with the PCM model. The difficulty level of the test items was between -0.83 and +0,84 which implied that the test items belonged to the good category because the value of the test items was between -2.0 and +2.0. The informative function of the total tests was relatively high for ability between -2.5 to +2.5. Thereby, the instrument developed can be used for measuring the inquiry ability of the physic subject of the senior high school students. The results of measurement showed that the inquiry ability of the learning participants in physic subject within the senior high schools in DIY was above average. Keywords: inquiry ability, physic subject in senior high schools, performance assessment